Peut-on parler d’une sociologie implicite du roman ? - David Ledent (Revue d'anthropologie des connaissances)
Since the 1990s in France, the idea of an “implicit sociology” of the novel has become progressively apparent in the social sciences which can consider this literary form as a tool for reflection. To consider it thus, is to place emphasis on the cognitive function of the novel as a useful source of sociological knowledge, a function which is nonetheless double-headed. The implicit sociology of the novel suggests a descriptive function and an analytical function both of which must be distinct from each other if we are to comprehend its possible uses by academic sociology. We can therefore identify three approaches of a sociology through literature, the first uses fictional story-telling as a possible illustration, the second involves using the descriptions employed by the novelist as material, and finally, the third involves viewing the novel as a laboratory of sociological thought.